The Art of Latina and Latino Elderhood
VI, 139 p.
Keywords: It is widely recognized that Latinos are a sizable and diverse population and that they are a young demographic. The median age of non-Hispanic white Americans is 58, whereas for Latinos it is 30. Perhaps this partially explains the dearth of attention afforded to the topic of aging Latinos by academic scholarship and the mainstream media. This book compellingly alerts us to the reality that there is a growing, aging Latino population about which we know very little and that deserves our attention. The book responds to this significant gap in our knowledge with an exciting set of academic articles and creative contributions that challenges not only our assumptions about Latinos and aging but also our thinking on the types of contributions in an academic context. The contributors make the case that the story of Latino elderhood is best conveyed through a truly multidisciplinary and interdisciplinary approach, bringing together public policy, humanistic social sciences, and artistic interventions. Previously published as a Special Issue in the journal: Latino Studies "Special Issue: The Art of Latina and Latino Elderhood".